Current insights into the German Lipoprotein Apheresis Registry (GLAR) – Almost 5 years on. (November 2017) - ,; Vogt, A.; Jaeger, B.R.; van Buuren, F.; Mellwig, K.P.; Klör, H.U.; Grützmacher, P.; Roeseler, E.; Julius, U.; Heigl, F.; Blume, H.; Schettler, V.J.J.; et al.
Abstract: Background: In recent years the Federal Joint Committee (G-BA), a paramount decision-making body of the German health care system required a reassessment of the approval of chronic lipoprotein apheresis therapy for regular reimbursement. Since 2005 an interdisciplinary German apheresis working group has been established by members of both German Societies of Nephrology. In 2009 the working group completed the indication for lipoprotein apheresis with respect to current cardiovascular guidelines and current scientific knowledge for the registry. In 2011 the German Lipoprotein Apheresis Registry (GLAR) was launched and data acquired over nearly 5 years can now be reported. Methods and results: All data were collected and analyzed during the time period 2012–2015. Over this time interval, 68 German apheresis centers collected retrospective and prospective observational data of 1.283 patients undergoing lipoprotein apheresis (LA) treatment of high LDL-cholesterol (LDL-C) levels and/or high lipoprotein(a) (Lp(a)) levels suffering from progressive cardiovascular disease (CVD). A total of 15, 167 documented LA treatments were investigated. All patients treated by LA exhibited a median LDL-C reduction rate of 68.6%, and a median Lp(a) reduction rate of 70.4%. Analogue to the Pro(a)LiFe pattern, patient data were analyzed and compared with respect to the incidence rate of coronary events (MACE) 1 and 2 years before the start of LA treatment (y−2 and y−1) and prospectively one year on LA treatment (y+1). During the first year of LA treatment a MACE reduction of 97% was be observed. In the years considered, LA treatment side effects occurred at a low rate (ca. 5%) and mainly comprised puncture problems. Conclusions: For the first time data generated by the GLAR shows that LA lowers the incidence rate of cardiovascular events in patients with high LDL-C and/or high Lp(a) levels, progressive CVD and maximally tolerated lipid lowering medication. In addition LA treatments were found to be safe, exhibiting a low rate of side effects.